Crystal structures and properties of two Cu(I) complexes based on Keggin-type clusters and diethyl 4, 4′-dicarboxy-2, 2′-biquinoline acid. Issue 10 (19th May 2018) - Lai, Jiajia; Duan, Xianying; Yang, Hui; Wei, Meilin
Abstract: Two proton-conductive Cu(I) complexes based on Keggin-type clusters, [Cu(debqdc)2 ]2 [HPW12 O40 ]·4H2 O (1 ), and [Cu(debqdc)2 ]2 [HPW12 O40 ]·debqdc·4H2 O (2 ), where debqdc is diethyl 4, 4′-dicarboxy-2, 2′-biquinoline, were simply synthesized at room temperature. The products were structurally characterized by elemental analyses, infrared spectroscopy, and single-crystal X-ray diffraction analyses. Single-crystal X-ray diffraction analyses revealed that both complexes crystallized in the triclinic space group P −1 and presented two three-dimensional supramolecular networks with one-dimensional hydrophilic channels via hydrogen-bonding interactions and π–π stacking interactions between the aromatic rings. In the [Cu(debqdc)2 ] + ion, debqdc acts as a bidentate nitrogen donor ligand in the chelating fashion. The bulky debqdc ligand constrains the Cu(I) metal center within such a rigid environment in a tetrahedral geometry. The two complexes exhibit good proton conductivities (10 −5 10 −4 S cm −1 ) at 100 °C in the relative humidity range 35 98%. The luminescence behaviors of these complexes in the solid state at room temperature have also been investigated. Upon excitation at 285 nm, both1 and2 display three main emission peaks centered at 470, 520, and 568 nm, respectively. Abstract :